Implementation of the learning process: Efforts to improve the quality of vocational education graduates - Ernawati Ernawati (ADGVI & Graduate School of Universitas Negeri Yogyakarta, 2021)
The quality of education is determined by a good management process, including the evaluation process of vocational education graduates. Furthermore, the purpose of this study is to evaluate the implementation of the learning process in vocational education programs, which includes an implementation of the teaching and learning process, the implementation of industrial training, lecturer skills in industrial supervision training, and encouraging entrepreneurship by lecturers to students. This study used a mixed-method design, and data were collected by questionnaires and depth-interview questions. The sample size is 218 graduates successfully collected using the total sampling technique. Data analysis used quantitative descriptive statistics (SPSS 23.0) and qualitative descriptive. Qualitative data support the quantitative results through interviews with five research informants. The results showed that graduates agreed that the teaching and learning process, the implementation of industrial training, lecturer skills in industrial supervision training, encouraging entrepreneurship by lecturers to students had gone well. In conclusion, the implementation of the vocational education program has been following the program's objectives. However, the results of the study showed that there are still weaknesses in the guidance from lecturers to students in the practice of opening a business and updating developments in related industries. Based on the results of this study, recommendations are made to focus on improving the process of implementing vocational education programs.